Mechanics and Strategies for Wrinkling Suppression: A Review - Zhang, Zhaojie; Zhao, Lingyu; Shi, Jidong (Frontiers in Mechanical Engineering, 2022)
Wrinkling is a well-known phenomenon observed at various length scales for diverse materials. Despite a variety of researches focusing on investigating wrinkling mechanisms and utilizing them to create surface patterns recently, wrinkling also brings about the loss of specific functional properties that were initially endowed to the thin films. For instance, wrinkling may result in the degradation of electrical and optical properties of the film; and the wrinkled films are easily delaminated. Therefore, it is still meaningful to find ways for the suppression of wrinkling on thin film, although the relevant works are far less than those utilize the surface instability to achieve certain structures. In this review, the approaches to restrain the emergence of wrinkles will be introduced. Following the introduction part, the numerical analysis for wrinkle generation will be first discussed, by which the key parameters determining wrinkles initiation and morphology will be provided. Then wrinkle suppression strategies by tailoring these parameters will be introduced in the following sections. This review aims to provide useful guidance for the future research for alleviating surface fluctuations and achieving desired device functionality.